Treatment coverage, barriers to care and factors associated with help-seeking behaviour of adults with depression and alcohol use disorder in Chitwan district, Nepal - Luitel, Nagendra Prasad (Department of Psychiatry and Mental Health, 2020)
Introduction: Globally, there is a substantial gap between the number of individuals in need of mental health care and those who receive treatment. It is reported that 86.3% people with anxiety, mood, or substance disorders in low and middle-income countries (LMICs) received no treatment in the 12 months preceding the survey. The Programme for improving mental health care (PRIME) aims to generate new evidence on implementation and scale up of mental health programs in primary health care settings to minimize this enormous treatment gap on mental health care, especially in the LMICs. The aim of this study was to report on the change in treatment coverage, barriers and other factors associated with help-seeking behaviour of adults with depression and alcohol use disorder (AUD) in Chitwan district, Nepal before and three years after implementation of the PRIME district mental health care plan (MHCP). Methods: The study was conducted in 10 Village Development Committees of Chitwan district in southern Nepal. The repeat population-based cross-sectional community survey applied a random sampling technique to select 1983 and 1499 adults in the baseline and the follow-up survey, respectively. The Patient Health Questionnaire (PHQ-9) and Alcohol Use Disorder Identification Test (AUDIT) were used to screen people with depression and AUD. Barriers for seeking mental health care were assessed by using a standardized tool, the Barriers to Care Evaluation Scale (BACE). Results: Overall, 11.7% (n=13) people with depression in the follow-up survey reported that they had received mental health treatment from any provider in the 12 months preceding the survey; this proportion was not significantly different from the proportion reported at the baseline (n=18; 8.1%;χ2=1.02, p=0.424). Similarly, the proportion of the participants receiving treatment for AUD from any provider at the follow-up survey (n=9; 10.3%) was also not significantly different than that found at baseline (n=5; 5.1%; χ2=1.68, p=0.235). Significant reductions were found in the overall BACE score (p=0.004) and the specific BACE domains scores pertaining to financial barriers (p<0.001); stigma (p=0.004) and lack of support (p<0.001) in the follow-up survey among participants with depression. In the AUD group, there was also a significant reduction between the baseline and follow-up survey in the overall BACE score (p=0.011) and the specific BACE domains scores pertaining to financial barriers (p<0.001) and lack of support (p<0.001). There was no association between socio-demographic characteristics and help seeking behaviour of the participants at the follow-up survey. Participants who reported greater cultural practices and beliefs were less likely (OR 0.65, 95% CI 0.46 – 0.92) to receive mental health care compared to those who reported less cultural beliefs and practices (p=0.015). Conclusion: The study found non-significant improvements in treatment coverage and significant reductions in barriers to mental health care following implementation of the PRIME district mental health care plan. The non-significant improvements in the treatment coverage could be explained by a number of potential factors, including lack of targeted community level interventions for specific barriers in the PRIME MHCP, the distal nature of the outcome in relation to the intervention, and the small number of screen positive participants. The key areas for improvement in the implementation of the district mental health care plan include establishment of confidential place for consultation in each health facility and targeted community awareness and sensitization programmes to improve help-seeking attitudes, intention and behaviour.